(untitled) (BIRDEM Medical Journal, 2012)
Better understanding of pathogenesis of Rheumatoid Arthritis (RA) has enabled researchers to introduce newer agents for treatment of RA. These new agents, known as biological response modifiers or biologics, singly or commonly, in combination with other conventional disease modifying anti-rheumatic drugs, seem to be better in patients acceptability, tolerance, clinical and radiological response. These drugs are responsible for significant immune-suppression, may result in sepsis and reactivation of per se latent infections. Some agents are suspected to be related to cancer development. The higher cost and significant adverse effects are important concerns in clinical use of biological agents in RA. DOI: http://dx.doi.org/10.3329/birdem.v2i1.12361 Birdem Med J 2012; 2(1) 44-51